PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIO VISUAL GERAK TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Afriliyanti, Lia; Rokayah; Poppy Anggraeni (JESA-Jurnal Edukasi Sebelas April, 2024)
This study aims to analyze the effect of the Problem Based Learning learning model on the critical thinking skills of fifth grade students of SDN Manangga, South Sumedang District. The method used in this research is pre-experiment using one group pretest-posttest design. The sampling technique in this study was total sampling. The sample in this study were 30 fifth grade students. The data collection techniques used were observation techniques and test techniques. The instruments used were observation sheets for the implementation of the learning model and critical thinking skills test questions. Data analysis techniques in this study are validity test, reliability test, difficulty test, normality test and t test, data analysis in this study was assisted by Microsoft Excel 2019. Based on the processing of the observation sheet for the implementation of the learning model, a percentage of 82% was obtained in the practical category. The t test results obtained a value of 22.58> 1.70 or t count> t table , then Ho is rejected and Ha is accepted, meaning that there are differences in students' critical thinking skills before and after using the Problem Based Learning learning model assisted by motion audio visual media. This can be seen based on the average posttest result of 75.33 while the average pretest value is 55.00. Based on the average value, the posttest average is greater, meaning that the posttest is better. It can be concluded that there is an effect of the Problem Based Learning learning model assisted by motion audio visual media on students' critical thinking skills in learning science material on natural events in grade V students of SDN Manangga.